Kualitas Pelayanan dan Reputasi Manajemen Terhadap Produk Bank BTN Syariah KCP Solo - Enik Tri Afrika; R. Taufiq Nur Muftiyanto; Esti Dwi Rahmawati (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2024)
This research aims at Service Quality and Management Reputation for Bank BTN Syariah KCP Solo Products. The approach used in this research is a quantitative approach. The sampling technique in this research was a purposive sampling technique with the sample used amounting to 96 respondents. The data collection technique uses online questionnaire distribution with the help of Google forms. Data analysis techniques in this research are validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression test, coefficient of determination test, f test and t test. Based on data research analysis, the results show that there is an influence of service quality on bank products, there is an influence of management reputation on bank products, the f test shows that there is a simultaneous influence of service quality and management reputation on bank products. The results of the coefficient of determination test show an r square value of 0.502, which means that the influence of the service quality variable (x1) and management reputation (x2) simultaneously on the bank product variable (y) is 50.2%..